Report of a Working Group on Barley: Seventh meeting, 10-12 May 2011, Nicosia, Cyprus - Knüpffer, H.; Maggioni, L.; Jalli, M.; Kolodinska Brantestam, A.; Fasoula, D.; Lipman, E.; Bioversity International (2011)
The seventh meeting of the ECPGR Barley Working Group (WG), organized in collaboration with the Agricultural Research Institute (ARI) of Cyprus, was held from 10 to 12 May 2011 in Nicosia, bringing together 24 members, 3 observers and the ECPGR Coordinator. The meeting covered a wide range of topics: implementation of “A European Genebank Integrated System” (AEGIS) by the Barley WG (approaches and aims for the European Barley Collection; criteria for Most Appropriate Accessions; quality standards criteria; species-specific maintenance protocols for wild Hordeum species as part of the AEGIS Quality System); precise genetic stocks of barley; collection of developmental mutants of barley and their potential use in pre breeding work; Trust multiplication project for cereals and legumes; characterization and evaluation (pre-breeding workshop and activities, ring tests update, breeding for climate change); in situ and on-farm activities in barley (Hordeum wild species in Europe, crop wild relatives of cultivated barley, conservation strategy for wild Hordeum species); documentation and information (the European Barley Database and EURISCO; the International Barley Core Collection); pre-breeding and joint research proposals (development of a disease resistance database; development of phenotype tests for abiotic stress resistance; evaluation of germplasm through ring tests; lobbying for pre-breeding at EU and national level; collaboration for joint project proposals; sharing of information and expertise).